PENERAPAN MODEL COOPERATIVE INTERGRATED READING AND COMPOSITION (CIRC) PADA PEMBELAJARAN IPA SISWA KELAS V SD NEGERI SUKOREJO - Ulfa Mariska; Tri Juli Hajani; Novianti Mandasari (Primary Education Journal Silampari (PEJS), 2023)
The purpose of this study was to find out whether the application of the Cooperative Integrated Reading And Composition (CIRC) learning model can significantly improve the science learning outcomes of fifth grade students at SD Negeri Sukorejo. This type of research uses a quasi-experimental method, the research design is One-Group Pretest-Posttest Design. Place and Time The research was carried out at SD Negeri Sukorejo, Stl Ulu Terawas District, Musi Rawas Regency with research time in odd semesters. The study population consisted of 24 students of class V SD Negeri Sukorejo, the research sample used saturated sampling technique. Pre-test and post-test data collection techniques with 21 multiple choice questions. From the results of data analysis using the Z-test with a significant level of α = 0.05 it was found that Zcount > Ztable (2.50 > 1.64), so it can be concluded that there are science learning outcomes for fifth grade students of SD Negeri Sukorejo by applying the Cooperative Learning Model Integrated Reading And Composition (CIRC). Keywords: Cooperative Integrated Reading And Composition (CIRC), Science Learning Outcomes